Spontaneous Internal Limiting Membrane Removal While Peeling Epiretinal Membrane - Ali Zain, Junaid Afzal, Irfan Qayyum Malik, Haroon Tayyab (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine the incidence of accidental internal limiting membrane removal in cases of Epiretinal membrane peel. Material and Methods: It was a prospective observational study. The study was done at Eye unit III Mayo hospital Lahore from 1st January 2014 to 30th June 2014. Twenty patients (11 males and 9 females) of Epiretinal membrane peeling were included in the study. In all the cases Epiretinal peeling was done by a single surgeon. After Epiretinal membrane removal brilliant blue dye was used to stain the internal limiting membrane and the surgeon observed the characteristic of internal limiting membrane, that whether it was removed spontaneously during the peeling of Epiretinal membrane or not. The main outcome measured was status of the ILM after ERM peel. Results: Out of 20 patients 11(55%) patients had spontaneous internal limiting membrane peeling during the removal of Epiretinal membrane, with only very minute remnants at some places. While 8 (40%) patients had intact ILM but it was damaged at various sites. While one patient had intact and undamaged ILM. Conclusion: Internal limiting membrane is frequently removed during ERM peeling. Staining with brilliant blue G facilitates its identification. Key Words: ILM Peel, Internal Limiting membrane, Epiretinal membrane.